The pivotal role of cardiac computed tomography angiogram and 18F-fluorodeoxyglucose positron emission tomography-computed tomography in the diagnosis of right sided endocarditis: a case report. Issue 1 (8th January 2019) - El Barzouhi, Abdelilah; Tanis, Wilco; van Gelder, Rogier E; Vriend, Joris W J
Abstract: Background: Infective endocarditis (IE) poses many clinical and diagnostic challenges. Echocardiography is regarded as the imaging modality of choice for the diagnosis of IE, and plays a key role in both the diagnosis and management of endocarditis. We report on a case in which one could have overlooked an endocarditis of a pulmonary homograft if one had relied on echocardiography alone. Case summary: A 38-year-old man presented with intermittent fever and fatigue for 1 month. He had undergone a Ross procedure for a bicuspid aortic valve stenosis at the age of 17 years. At the age of 36 years a valve-sparing aortic root replacement was performed because of aortic root dilatation. Besides a systolic murmur 3/6 noted at the left sternal border, physical examination was normal. Multiple blood cultures grew Streptococcus mitis . Both transthoracic and transoesophageal echocardiogram could not detect any signs of endocarditis. As endocarditis can be overlooked due to reverberations and acoustic shadowing, we performed 18 F-fluorodeoxyglucose positron emission tomography-computed tomography (FDG-PET/CT) and cardiac computed tomography angiogram (cardiac CTA). Both imaging modalities showed large vegetations attached to the pulmonary homograft. Discussion: Endocarditis poses diagnostic challenges. While echocardiography is the cornerstone of imaging, one may overlook a pulmonary homograft endocarditis due to reverberations and acoustic shadowing. Therefore, if clinical suspicion of endocarditis is strong, one should consider additional imaging by means of cardiac CTA and/or 18 F-fluorodeoxyglucose positron emission tomography-computed tomography imaging to assess valves in pulmonary position, especially in those whom have had prior surgical intervention at this location.